Improving MRI Surface Coil Decoupling to Reduce B1 Distortion - (:unkn) unknown (My University, 2014)
As clinical MRI systems continue to advance, larger focus is being given to image uniformity. Good image uniformity begins with generating uniform magnetic fields, which are easily distorted by induced currents on receive-only surface coils. It has become an industry standard to combat these induced currents by placing RF blocking networks on surface coils. This paper explores the effect of blocking network impedance of phased array surface coils on B1 distortion. It has been found and verified, that traditional approaches for blocking network design in complex phased arrays can leave undesirable B1 distortions at 3 Tesla. The traditional approach of LC tank blocking is explored, but shifts from the idea that higher impedance equals better B1 distortion at 3T. The result is a new design principle for a tank with a finite inductive reactance at the Larmor Frequency. The solution is demonstrated via simulation using a simple, single, large tuning loop. The same loop, along with a smaller loop, is used to derive the new design principle, which is then applied to a complex phased array structure.
Keywords: Blocking; Decoupling; Distortion; Magnetic Field; MRI; Surface Coil